Apical periodontitis and related risk factors: cross-sectional study - Correia-Sousa, Joana (2015)
Objectives: The aim of this cross-sectional study was to investigate an association between the prevalence of root-filled teeth (RFT) or apical periodontitis (AP) and some systemic conditions or smoking habits in an adult Portuguese population. Methods: Medical histories, including age, gender, presence of cardiovascular disease (CVD), diabetes mellitus (DM), allergies, smoking status, and endodontic treatment data of 421 patients (10,540 teeth) were recorded. The prevalence of root filled teeth and the periapical status were assessed through panoramic radiographies. Periapical status was classified according to the Periapical index and AP was defined as PAI-score ≥3. Statistic analysis was performed with PASW Statistics 20.0 using qui-square tests, odds-ratio and confidence intervals (95%). Results: The overall prevalence of AP and RFT was 2.2% and 4.2%, respectively. RFT increased the possibility of having AP (p< 0.0001). Men's group showed a higher percentage of teeth with AP (p< 0.0001), less RFT (p = 0.05) and more residual roots (2.3%). Smoking increased the probability of having AP (p = 0.002) and RFT (p = 0.045). A positive correlation was observed between RFT and DM (p = 0.040). No statistically significant difference was found between AP and CVD, DM or allergies neither between RTF and CVD or allergies. Conclusions: The higher prevalence of AP and/or RFT in smoker subjects and in diabetic patients can suggest a relationship between oral and systemic health. More epidemiological studies are required before definitive conclusions can be made.